Book Review: Negotiating Terrain in Local Governance: Freedom, Functioning and Barriers of Women Councillors in India Authors: Riya Banerjee & Gopa Samanta Part of Series of Book Edited by Carlos Nunes Silva ISBN 978-3-030-60663-3 ebook: 106, 99 €; hardcover: 135, 19 € Included format: EPUB, PDF https://www.springer.com/gp/book/9783030606626 Publisher: Springer Nature, Switzerland AG 2020. Issue 2 (2021) - Paul, Norvy; Pulla, Venkat
No abstract available